THE SAFETY, TOLERABILITY, AND EFFECTIVENESS OF BIOLOGICS/SMALL MOLECULE THERAPY IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE AND CIRRHOSIS. (21st January 2021) - Li, Muyi; Khan, Sameer; Proctor, Deborah; Gaidos, Jill; Al-Bawardy, Badr
Abstract: Introduction: Biologic agents and small molecules have been shown to be effective and relatively safe in the treatment of inflammatory bowel disease (IBD). However, data is lacking regarding the use of these agents in patients with IBD and concomitant cirrhosis. The aim of this study is to examine the safety, tolerability and effectiveness of biologics and small molecules in patients with IBD and concomitant cirrhosis. Methods: This is a retrospective study of adult patients diagnosed with both IBD and cirrhosis (by liver biopsy or Fibroscan) treated with biologic agents or small molecule agents between 2012 and 2020 within the Yale-New Haven Hospital system. We included patients on tofacitinib or any of the following biologic agents: infliximab, adalimumab, certolizumab pegol, golimumab, vedolizumab, ustekinumab. Primary outcomes were rates of adverse events (infection, infusion reaction, IBD-related hospitalization) and mortality. Secondary outcomes were clinical remission (defined by the physician global assessment) and mucosal healing (Mayo endoscopic score of 0 or 1 for ulcerative colitis (UC) and absence of erosion/ulcerations in Crohn's disease (CD)). Results: A total of 18 patients (72% CD, 28% UC) with median age of 50 (26–73) years were included (Table 1 ). Decompensated cirrhosis was present in 33.3% of the population prior to initiation of biologic/small molecule therapy. The most common etiology of cirrhosis was primary sclerosing cholangitis at 38.9%. IBD therapy included: infliximab/adalimumab (44.5%), vedolizumab (27.7%), and ustekinumab (22.2%) and tofacitinib (5.6%). A total of 4 patients (22.2%) were on concomitant corticosteroid therapy and 3 on combination therapy with thiopurines (Table 2 ). Adverse events occurred in 27.7% (n=5; 1 infusion reaction and 4 infections). The 4 patients with infections included: 2 on infliximab/adalimumab, 1 on ustekinumab, 1 on vedolizumab. Two of these patients were on concomitant thiopurines and 1 on corticosteroid. Biologic therapy was stopped in 3 patients, 2 for non-response and 1 for an infusion reaction. Mortality rate was 11% and all were liver-related. Clinical remission was achieved in 66.7% and mucosal healing was noted in 72.7% (8/11). Conclusions: In this cohort of patients with IBD and cirrhosis, biologic/small molecule therapies were effective for IBD. Approximately a quarter of patients experienced adverse events that were mainly due to infections. Larger studies are needed to elucidate the relative safety of different biologic agents and small molecules in IBD patients with cirrhosis.